Closure in the Novel. - Torgovnick, Marianna (Princeton Legacy Library, 2017)
Drawing on a wide range of nineteenth- and twentieth-century English, French, American, and Russian novels, Marianna Torgovnick demonstrates the variety and complexity of the process by which a work reaches an appropriate conclusion. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.